Efforts to Improve Student Learning Outcome in Bahasa Indonesia on Map Material through Problem Based Learning Model - Rosmiati, Cucu; Carlian, Yayan (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research is motivated by the low learning outcomes of students in Class II of MI Nurul Falah Kota Cimahi, which is caused by the Indonesian language learning process still being teacher-centered, with teachers following the habit of directly presenting the material and then evaluating students through exercises. The aim of this study is to improve students' learning outcomes in the Indonesian language subject, specifically in the topic of